MANFAAT KETERLIBATAN PETANI DALAM POLA KEMITRAAN AGRIBISNIS SAYURAN DI JAWA BARAT - Ninuk Purnaningsih; Basita G. Sugihen (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2008)
The main problems for vegetable farmers are low technology and intensive use of pesticide, therefore farmers cannot produce vegetables with good quality continually. By applying agribusiness partnership it is expected the farmers would be able to overcome the limitation of technology and capital for small farmers attainment a good quality of vegetables, and problem of marketing. This study was aimed to analyze benefit involvement of farmers in agribusiness partnership. Collective case study method was used in five agribusiness companies and one co-operation which applying partnership of agribusiness in West Java: i.e. Bogor, Cianjur, Bandung, and Garut. The population are farmers around company and co-operation, the unit of analysis is farmers household counted of the 285 farmers. Involvement of farmers in partnership has effect on the improvement of farmers income, the use of technology (production and handling), appropriate pesticide use use, labor absorption, and capital usage. Involvement of farmers in partnership also has effect on continuity of farmers business.